Depuration time and sublethal effects of microcystins in a freshwater fish from water supply reservoir. (November 2018) - Calado, Sabrina Loise de Morais; Santos, Gustavo Souza; Leite, Talitha Pires Borges; Wojciechowski, Juliana; Nadaline, Mário; Bozza, Deivyson Cattine; Magalhães, Valéria Freitas de; Cestari, Marta Margarete; Prodocimo, Viviane; Silva de Assis, Helena Cristina
Abstract: Microcystins (MCs) are hepatotoxins that have been considered to be a worldwide problem due the effects that they can cause to environmental and human health systems. The Iraí Reservoir, located in the South of Brazil, is used as a water supply and MCs concentrations have been reported in this ecosystem. This study aimed to determine the MCs concentrations in the Iraí Reservoir and to evaluate the MCs depuration time and the health of Geophagus brasiliensis using biomarkers. Water and fish samples were collected in the Iraí Reservoir from August 2015 to May 2016. Phytoplankton and chemical analyses were conducted using water samples and the fish were divided into two groups; the Immediate Group (IMM) and the Depuration Group (DEP). In the IMM group, the blood, liver, muscle, brain and gills were collected, in order to evaluate the genotoxic, biochemical and chemical biomarkers. The DEP group was used in the depuration experiment for 90 days, and after this period the fish were submitted to the same procedure as the IMM group. Our results suggested that fish accumulated MCs and it may have caused oxidative stress, neurotoxicity and molecular damage. Furthermore, MCs concentrations increased during the depuration time and it resulted in molecular damage over the first 30 days. After 90 days, the recovery of the antioxidant system occurred. The depuration started on the 15th day, however, the toxins were still present in the samples. Therefore, the effects and the persistence of MCs are a risk to environmental systems and human health. Highlights: The Iraí Reservoir is contaminated by Microcystins (MCs). Fish have accumulated MCs above the established limit for human consumption. Neurotoxicity, oxidative stress, molecular and liver damage were observed in fish. A recovery of the antioxidant system and molecular damage was present 90 days after. After the depuration time, MCs were still detected in the muscles of the fish.